EVALUATION OF THE IMPACT OF WORKING CAPITAL CREDIT AND PEOPLE'S BUSINESS CREDIT ON BANK PROFITABILITY: EMPIRICAL STUDY AT PT. BANK NEGARA INDONESIA (PERSERO) TBK BULUKUMBA BRANCH - haeruddin; Ibrahim Ibrahim; Rahmi Rahmi; Hisnol Jamali (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This research aims to analyze the influence of Working Capital Credit and People's Business Credit (KUR) on company profitability at PT. Bank Negara Indonesia (Persero) Tbk, Bulukumba Branch Office. This study uses secondary data obtained from banks' annual financial reports for the 2017-2021 period. The analysis was carried out using multiple linear regression to test the partial and simultaneous influence of the two types of credit on profitability. The research results show that Working Capital Credit has a significant influence on bank profitability, which is in line with the theory that this credit provides the liquidity needed for operations and increases interest income. In addition, KUR also shows a significant influence on bank profitability, which supports the importance of this credit in expanding financial inclusion and increasing the customer base. Simultaneously, the combination of Working Capital Credit and KUR makes a significant contribution to profitability, which shows the importance of credit portfolio diversification in improving bank financial performance. The uniqueness of this research is its focus on the simultaneous influence of Working Capital Credit and KUR on bank profitability, which is rarely analyzed in previous studies. Additionally, this research was conducted in the context of regional banks, which provides a new perspective on credit management and profitability outside of large or national banks. These findings provide an important contribution to the literature on credit management and bank financial performance, as well as providing practical guidance for bank management in optimizing credit strategies to increase profitability. This research also provides insight for future researchers to develop further studies that can explore other variables that influence bank profitability and can enrich understanding of the dynamics of credit management in the banking sector.